Pemberdayaan Masyarakat (Kader Kesehatan dan Ibu Balita) Melalui Pengenalan Aplikasi Primaku di Posyandu Bukit Tinggi Harapan 2 Desa Dete - Herni Hasifah; Iga Maliga; Ana Lestari; Nur Arifatus Sholihah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The Primaku application was introduced and launched by the Indonesian Pediatric Association to facilitate early and continuous monitoring of children's growth and development. However, there are still many people who do not understand how to use this technology-based Primaku application. The purpose of this activity is to increase the knowledge and skills of the community, especially Posyandu cadres and mothers of toddlers, in monitoring the growth and development of infants and young children to prevent stunting. The problem-solving method is carried out by providing training on how to use the Primaku application and demonstrating how to assess children's growth and development using the Primaku application. Based on the results of the activity, it shows that the participants have good knowledge in understanding and using the Primaku application as a tool to monitor children's growth and development. with this activity, Posyandu cadres and mothers toddler can continue to update the latest information on children's growth and development.